2019
DOI: 10.1111/aogs.13585
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic lower uterine segment thickness after prior cesarean section to predict uterine rupture: A systematic review and meta‐analysis

Abstract: Abbreviations: SROC, summary receiver-operating characteristics; TOLAC, trial of labor after cesarean section; VBAC, vaginal birth after cesarean section. AbstractIntroduction: Cesarean section rates are increasing with a decrease in the rate of trial of labor after cesarean section. The objective of this study was to systematically review the predictive characteristics of sonographic measurement of lower uterine segment thickness for uterine rupture during labor. Material and methods:The review was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…These complications can occur sequentially or independent of one another. 34 A recent meta-analysis examining the uterine thickness after prior CS concluded that a lower uterine thickness of <2 mm suggests an increased risk of uterine rupture, 35 , 36 highlighting the importance of measuring the uterine thickness, especially within the lower uterus, after a previous CS. The literature also suggests that the size of a patient’s isthmocele can impact the risk of future complications; specifically, large diverticula (RMT of ≤2.2 mm) can increase the risk of scar dehiscence up to 42.9%.…”
Section: Discussionmentioning
confidence: 99%
“…These complications can occur sequentially or independent of one another. 34 A recent meta-analysis examining the uterine thickness after prior CS concluded that a lower uterine thickness of <2 mm suggests an increased risk of uterine rupture, 35 , 36 highlighting the importance of measuring the uterine thickness, especially within the lower uterus, after a previous CS. The literature also suggests that the size of a patient’s isthmocele can impact the risk of future complications; specifically, large diverticula (RMT of ≤2.2 mm) can increase the risk of scar dehiscence up to 42.9%.…”
Section: Discussionmentioning
confidence: 99%
“…At least two main shortcomings regarding ultrasound, for evalution of p-CS scar, should raise concern. First, it is heavily operator-dependent, second, the definition of LUS thickness on ultrasound is not standardized, inconformity was shown in many aspects, including between 2D thickness and 3D volume [16], or whether the bladder wall should be excluded [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…Scar length was 0.66 ± 0.45 cm, width was 1.18 ± 0.53 cm and minimal scar thickness was 0.44 ± 0.22 cm. Scar volume was assumed as cuboid and calculated by multiplication of thickness, width and length, which was 0.35 ± 0.36 cm 3 .…”
Section: Scar Morphological Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The same procedure showed accuracy among pregnant women with a reported prior spontaneous preterm birth history 3 . In addition, lower uterine segment's small thicknesses measured by ultrasound predict organ dehiscence or rupture during labor among prior cesarean section cases 4,5 …”
Section: Introductionmentioning
confidence: 99%